Syphilis in pregnancy at Public Health Centre III North Denpasar - Odilia Dea Novena; Gusti Ayu Vina Mery Giovani (Bali Dermatology Venereology and Aesthetic Journal, 2021)
Introduction: Syphilis is a sexually transmitted infection (STI) caused by the bacterium Treponema pallidum. Syphilis in pregnancy is often asymptomatic, so early detection of syphilis is needed to prevent a poor pregnancy outcome and transmission of infection to the baby. Case: A 25-year-old woman, pregnant with her second child at 24 weeks of gestation, came without any health complaint for a routine prenatal check-up. On syphilis screening, reactive TPHA and RPR titer of 1:2 were found. The patient was diagnosed with syphilis infection in pregnancy. The patient has been treated with Benzathine Benzylpenicillin 2.4 million IU intramuscular injection once a week for 3 consecutive weeks. Conclusion: Syphilis is a sexually transmitted infection that infects pregnant women. Treponemal transmission in pregnant women was detected early in the ninth week of pregnancy. The diagnosis of syphilis was made by dark-field microscopy, treponemal antibody tests (TPHA, FTA-ABS), and non-treponemal antibody tests (VDRL, RPR). Penicillin is the gold standard therapy for syphilis in pregnant women.